Intellectual structure of knowledge in iMetrics: A co-word analysis. Issue 3 (May 2017) - Khasseh, Ali Akbar; Soheili, Faramarz; Moghaddam, Hadi Sharif; Chelak, Afshin Mousavi
Highlights: In order to build a complete structure of subjects areas in iMetrics, both types of keywords are included in this study. Application of hierarchical clustering analysis led to the formation of 11 subject clusters in iMetrics. Analysis of the strategic diagram showed two most comprehensive themes of iMetrics. In spite of their similarity with those ofCourtial (1994), clusters in this study were different from several aspects. Abstract: As an iMetrics technique, co-word analysis is used to describe the status of various subject areas, however, iMetrics itself is not examined by a co-word analysis. For the purpose of using co-word analysis, this study tries to investigate the intellectual structure of iMetrics during the period of 1978 to 2014. The research data are retrieved from two core journals on iMetrics research ( Scientometrics, and Journal of Informetrics ) and relevant articles in six journals publishing iMetrics studies. Application of hierarchical clustering led to the formation of 11 clusters representing the intellectual structure of iMetrics, including "Scientometric Databases and Indicators, " "Citation Analysis, " "Sociology of Science, " "Issues Related to Rankings of Universities, Journals, etc., " "Information Visualization and Retrieval, " "Mapping Intellectual Structure of Science, " "Webometrics, " "Industry–University–Government Relations, " "Technometrics (Innovation and Patents), "Scientific Collaboration in Universities", and "Basics of Network Analysis." Furthermore, a two-dimensional map and a strategic diagram are drawn to clarify the structure, maturity, and cohesion of clusters.